PEMANFAATAN MEDIA SOSIAL DALAM PENYAMPAIAN INFORMASI DAN KONSULTASI HUKUM OLEH MAHASISWA HUKUM - Iron Fajrul Aslami; Erika Prima Tiara; Martinius Rambe Purba (Jurnal Abdimas Bina Bangsa, 2024)
Bina Bangsa University Law Faculty students took the initiative to provide community service through legal consultations using social media. By taking advantage of advances in information technology, we have opened the door for easier and more affordable access for individuals who need legal advice or information. Through social media platforms, Law Students can share knowledge and answer questions, as well as provide free advice accompanied by law lecturers to people who need legal assistance. In this way, not only helping the community in overcoming legal problems, but also increasing legal awareness in general. As an academic activity that shows the commitment of Bina Bangsa University law students in serving and making a positive contribution to society through the use of social media as an effective service tool